Manajemen Penerimaan Peserta Didik Baru di SDIT Ki Hajar Dewantoro Kecamatan Tambun Selatan Kabupaten Bekasi - Baharuddin Baharuddin; Diyah Yuli Sugiarti; Dewi Aryanti; St Rajiah; Nurhaeni Nurhaeni; Burhan Burhan (Alignment:Journal of Administration and Educational Management, 2020)
This study aims to analyze the management of admission of new students at SDIT Ki Hajar Dewantoro. This research uses descriptive qualitative research methods. From the results of the study, management analysis of new student admissions uses SWOT analysis. By looking at strengths, weaknesses, opportunities and threats so the school knows and can be used as input for the coming year, so the number of new students increases from year to year. In conclusion, school management plans all school activities and programs including; the existence of a school program as a hallmark of a superior school / program, school promotion, how schools implement their long, medium and short term work plans, and collaborative efforts in school management between school principals, teachers, parents, students and the community so that schools can be managed effectively. Keywords: Management Analysis, Students